DESIGN OF ANDROID-BASED LEARNING MEDIA IN REFRIGERATION ENGINEERING COURSES - Ardipamungkas, Rakensa Satria; Komaro, Mumu (Universitas Pendidikan Indonesia, 2023)
Learning media in Refrigeration Engineering courses are still fairly monotonous, the media used at this time is only power point. The use of android-based media can be said to be rarely used in lectures today. Based on these problems, an android-based learning media is needed. The purpose of this research is to create and assess the feasibility of android-based learning materials in refrigeration engineering courses, especially refrigeration component material. This research method uses the DBR (Design Based Research) method. The research subjects are aimed at Refrigeration and Air Conditioning students in the Department of Mechanical Engineering Education who have and are contracting refrigeration engineering courses. Validation of learning media was carried out by two experts, namely material experts and media experts. The results of the assessment of learning media are said to be valid with a score of 85.3% by media experts, and a score of 82% by material experts, and a response value of 83.5% by students.